PENGELOLAAN MUSYAWARAH GURU MATA PELAJARAN UNTUK MENINGKATKAN KOMPETENSI GURU MATA PELAJARAN EKONOMI - Lili Yulianti; Rohiat Rohiat; Aliman Aliman (UNIVERSITAS BENGKULU, 2017)
The purpose of this research is to know the managemen of the Economic Subject Teachers' Meeting in improving the Competence of Economics Teachers in South Bengkulu Regency. The research method is qualitative descriptive. Data collection techniques through interviews, observation and documentation studies. Research Subject. High School Economics teachers / MA South Bengkulu. The result of the research is the existence of program or outline of activity plan and other tools that will be needed in every meeting prepared by MGMP board. Detailed teaching tools owned by teachers, Implementation of follow-up program based on evaluation and analysis of MGMP program and activities.